Identity Complexity’s Influence on Multicultural Families’ Ethnic Identity Development and Acculturation Outcomes: A Qualitative Study among Binational (Estonian–Foreign) Parents in Estonia - Gabriel Alberto Ceballos Rodriguez (Genealogy, 2024)
For multicultural family members who live in cosmopolitan environments, concepts such as ethnic identity and integration have different significance. Some individuals can report, for example, that ethnic identity and integration have never played an important role in their lives and even feel that they represent old-fashioned notions from which modern societies should rather move on. For others, these concepts are much more relevant and are experienced in more challenging and complex ways. This article explores the influence that identity complexity—a cognitive disposition to perceive overlaps between different social identities, plays in this process. Forty parents of Estonian–foreign children (a traditionally cosmopolitan segment) were interviewed in Estonia and prompted to talk about topics such as their own ethnic identity(ies), their (and their family’s) feelings of integration into the Estonian society, and the way in which they represent their children’s ethnic identities, e.g., mostly Estonian/foreign, fifty–fifty, global citizen, etc. Thematic analysis combined with intersectionality suggests that there are associations between the identity complexity of interviewees and their attitudes towards these topics. Furthermore, results show that beyond the traditional dichotomy of high vs. low identity complexity, some interviewed parents have transitioned from higher to lower levels of identity complexity and vice versa at different times in their lives for different reasons. This study sheds light on identity complexity as a relevant predictor of acculturation and ethnic identity development outcomes among multicultural family members. It also contributes to the literature on cosmopolitan populations as a diverse group.